2015
DOI: 10.1016/j.eurpolymj.2015.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Improving humidity-controlled solvent annealing processes for block copolymer poly(ethylene oxide)-b-polystyrene

Abstract: a b s t r a c tThis paper addresses two challenges in humidity-controlled solvent annealing of poly (ethylene oxide)-b-polystyrene thin films: (1) reduction in annealing time by nearly an order of magnitude for toluene under high humidity, which is achieved by decreasing the annealing chamber volume; (2) utilization of two industry-benign solvents, methyl ethyl ketone (MEK) and propylene glycol monomethyl ether acetate (PGMEA), to achieve ordered surface patterns under high humidity. When toluene is employed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 61 publications
1
10
0
Order By: Relevance
“…The presence of solvent vapor plasticizes polymer films while also swelling the BCP domains and mediating block interactions. During SVA, polymer films therefore freely reorganize to adopt a new equilibrium morphology as defined under solvent swollen conditions 99–101 . However, measurements of the quenched state following SVA are complicated by chain collapse, gradients in solvent flow, and surface dewetting upon solvent removal.…”
Section: Polymer Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of solvent vapor plasticizes polymer films while also swelling the BCP domains and mediating block interactions. During SVA, polymer films therefore freely reorganize to adopt a new equilibrium morphology as defined under solvent swollen conditions 99–101 . However, measurements of the quenched state following SVA are complicated by chain collapse, gradients in solvent flow, and surface dewetting upon solvent removal.…”
Section: Polymer Applicationsmentioning
confidence: 99%
“…During SVA, polymer films therefore freely reorganize to adopt a new equilibrium morphology as defined under solvent swollen conditions. [99][100][101] However, measurements of the quenched state following SVA are complicated by chain collapse, gradients in solvent flow, and surface dewetting upon solvent removal. For example, Zhang et al showed that thermally annealed PS-b-P2VP films with cylinders, initially oriented perpendicular to the substrate, exhibit dewetting after SVA, with parallel cylinders near the dewetted regions.…”
Section: Block Copolymer Self-assemblymentioning
confidence: 99%
“…[122][123][124] Notably, a suitable selection of the casting solvent and ambient atmosphere conditions can lead to vertically ordered BCP morphologies aligned by the solvent evaporation front. [125][126][127] BCP-evaporating solvent interactions can be leveraged to control macroscopic orientation of domains in deposited thin films. Kowalewski et al utilized the zone casting process, originally developed for obtaining large-area arrays of small molecule single-crystals 128 in which BCP solution is cast from a slit-shaped nozzle onto a slowly moving substrate (Fig.…”
Section: Simultaneous Casting and Annealing Methodsmentioning
confidence: 99%
“…Long tubes may also hamper fast changes of conditions. Chambers with a very small volume and evacuation of the sample chamber before injection of liquid solvent [40,211] have been proposed. This way, the time needed for SVA may be reduced from several hours to several minutes.…”
Section: New Approaches To Svamentioning
confidence: 99%
“…Combining a nonselective with a selective solvent or two solvents being selective for either block and varying the mixing ratio may overcome these limitations and pave the way for a systematic variation of the degree of swelling of the different microdomains. Very detailed studies of the influence of the properties of solvent mixtures on the thin film structures have been reported; however, so far mostly ex-situ investigations have been carried out[92,211,[213][214][215][216][217][218][219].…”
mentioning
confidence: 99%